Evaluation of Urinary Neutrophil Gelatinase Associated Lipocalin (NGAL), as an Early Biomarker and Prognostic Factor of Contrast Induced Acute Kidney Injury (CI-AKI) following Cardiac Catheterization - Nessa, Azizun; Ahmed, Masud; Fakir, Md Amzad H; Mostafi, Mamun (Journal of Bangladesh College of Physicians and Surgeons, 2016)
Acute kidney injury (AKI) usually detected by s. creatinine, which rises after 48 hrs of insult causes delay in diagnosis and to take preventive or therapeutic measures. Hence amongst many neutrophil gelatinase associated lipocalin (NGAL) is emerging as early, sensitive, and most promising biomarker of AKI both in urine and plasma. This prospective cross sectional observational study was carried out in Combined Military Hospital (CMH) Dhaka from October 2011 to March 2012. A total of willing 100 adult patients undergoing elective coronary angiogram (CAG) with normal kidney function were included in this study. Our study defined contrast induced AKI (CI-AKI) as rise of serum creatinine by >25% or e0.5 mg/dl from baseline after exposure to contrast media and urine NGAL e100 ng/ml was taken as cut off value to predict AKI as calculated by ROC curve. The main outcome measures were urine NGAL at 4 hrs and serum creatinine at 48 hrs after CAG. Significant elevation of urine NGAL was noted in 9 patients after 4 hrs of CAG, of them 8 (8%) patients developed raised s. creatinine (AKI) after 48 hrs. Patient demographics and procedural factors were although statistically significant in few instances but none was predictive of AKI. J Bangladesh Coll Phys Surg 2015; 33(3): 133-139